4-GNSS radio occultation satellite constellation design based on Dual-gate uniformity evaluation index. (January 2017) - Wang, Jue-yao; Liang, Bin
A brand-new area of low earth orbit satellite constellation research has been expanded by global navigation satellite system (GNSS) radio occultation (RO) atmosphere sounding technology in the last decade. The possibility of reducing the sounding satellites while keeping the amount of atmosphere soundings increasing to produce low-cost meteorological data product is investigated, and a constellation capable of receiving the RO signals from all the 4-GNSS, such as GPS, GLONASS, Galileo, and Compass, is proposed in this paper. This paper focuses on the mathematical problems on the design of 4-GNSS RO satellite constellation. A forward GNSS RO sounding simulation algorithm based on ideal atmosphere model and two-dimensional radial tracing algorithm is presented for a rapidly and accurately sounding performance prediction of 4-GNSS RO satellite constellations. Then, an improved uniformity evaluation factor named Dual-gate is established for 4-GNSS RO satellite constellation optimization design, which is a combination of the uniformity evaluation factors for the latitudinal distribution of RO soundings and those for the gridding uniformity. On the basis of low earth orbit satellite orbit dynamics and spherical geometry, the impacts of partial constellation parameters on the amount and coverage performance accorded with Dual-gate uniformity evaluation index are derived, and a series of design criteria of 4-GNSS RO satellite constellation are summarized. A simplified 4-GNSS RO satellite constellation model is built on the basis of the design criteria, and an improved ant colony algorithm is used to optimize the parameters of a 4-GNSS RO constellation including as many satellites as COSMIC-2. The simulation result shows that this 4-GNSS RO constellation is capable of obtaining near 3000 atmosphere soundings per 3 h. It obtains 13% more soundings than COSMIC-2 with the same 4-GNSS RO sounding devices, and the uniformity of soundings is increased by 9%.